Effects of competition and its outcome on serum testosterone, cortisol and prolactin - Suay, F.; Salvador, A.; Gonzalez-Bono, E.; Sanchis, C.; Martinez, M.; Martinez-Sanchis, S.; Simon, V. M.; Montoro, J. B. (Psychoneuroendocrinology, 1999)
In various species, competitive encounters influence hormonal responses in a different way depending on their outcome, victory or defeat. This study aimed to investigate the effects of sports competition and its outcome on hormonal response, comparing it with those displayed in situations involving non-effort and non-competitive effort. To this end, serum testosterone (T), cortisol (C) and prolactin (PRL) were measured in 26 judoists who participated in three sessions (control, judo fight and ergometry). The relationship between hormonal changes and psychological variables before and after the fight were also analysed. Our results showed a hormonal response to competition, which was especially characterized by an anticipatory rise of T and C. Depending on outcome, significant higher C levels were found in winners in comparison to losers through all the competition but not in T or PRL, both groups expending a similar physical effort. Furthermore, similar hormonal responses to the fight and to a non-competitive effort with the same caloric cost were found, other than with PRL. Winners showed a higher appraisal of their performance and satisfaction with the outcome, and perceived themselves as having more ability to win than losers, although there were no significant differences in motivation to win. Finally, the relationships found between T changes in competition and motivation to win, as well as between C response and self-efficacy suggest that in humans hormonal response to competition is not a direct consequence of winning and losing but rather is mediated by complex psychological processes.